"Chic but Scrupulous, Down to the Very Last Stitch"1: "Style Ethics" in American Vogue. (4th May 2017) - Jones, Katie Baker; Hawley, Jana M.
Abstract: Sustainability in fashion becomes a more pressing matter year after year. Growing consumer awareness of the issues paired with governmental regulation has forced the industry to start taking action. Vogue has also incrementally adjusted to the changing demands of the modern socio-cultural context in which it operates. In this article the discursive practices employed by Vogue to construct a discourse on sustainable fashion in its "Style Ethics" editorials, 2009–2013 are explored. Thirty-seven "Style Ethics" editorials were examined using Critical Discourse Analysis (CDA). The article argues that Vogue 's incorporation and appropriation of the sustainable fashion discourse has the potential to shape and/or alter perceptions of sustainable fashion. Vogue 's cultural capital grants it a position of power in meaning construction for the industry. Thus, understanding the magazine's perspective on sustainable fashion can reveal potential sources of problematic perceptions that may hinder or distort acceptance of sustainable fashion goods and practices.